2015
DOI: 10.1007/s40572-015-0052-1
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Exposure and Epigenetic Alterations: Recent Findings Based on the Illumina 450K DNA Methylation Array

Abstract: Arsenic is a major public health concern worldwide. While it is an established carcinogen and associated with a number of other adverse health outcomes, the molecular mechanisms underlying arsenic toxicity are not completely clarified. There is mounting evidence from human studies suggesting that arsenic exposure is associated with epigenetic alterations, including DNA methylation. In this review, we summarize several recent human studies that have evaluated arsenic exposure using the Illumina HumanMethylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 61 publications
0
38
0
Order By: Relevance
“…There is emerging evidence linking epigenetic changes, such as alterations in DNA methylation, to the mechanisms behind certain As-induced toxicity [reviewed in (Argos 2015; Ren et al 2011)]. DNA methylation has a high plasticity in utero, making embryogenesis a particularly susceptible window for epigenetic alterations that can alter disease susceptibility later in life (Hochberg et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is emerging evidence linking epigenetic changes, such as alterations in DNA methylation, to the mechanisms behind certain As-induced toxicity [reviewed in (Argos 2015; Ren et al 2011)]. DNA methylation has a high plasticity in utero, making embryogenesis a particularly susceptible window for epigenetic alterations that can alter disease susceptibility later in life (Hochberg et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Recent human studies have indicated that As exposure early in life may cause alterations of DNA methylation (reviewed in Argos 2015; Martin and Fry 2018). For example, we have reported associations between prenatal exposure to As and differentially methylated CpG sites in umbilical cord blood, especially of boys, with stronger effect for exposure in early versus late pregnancy (Broberg et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This is a public health concern because arsenic is a known human carcinogen and chronic exposure is associated with the development of skin, lung, bladder, kidney, liver, and, potentially, prostate cancer. 1 Particularly, early life exposure to arsenic has been associated with the development of many latent health effects including carcinogenesis. 2 Human ecological studies from the Antofagasta region of Chile have associated prenatal and early childhood exposure to arsenic from contaminated municipal water with increased risk of lung and bladder cancer later in life.…”
Section: Introductionmentioning
confidence: 99%
“…2 Several human studies have evaluated the impact of prenatal arsenic exposure on the cord blood and whole blood epigenome. 1 Among these epidemiological studies evaluating cord blood or whole blood DNA methylation, no common loci have been identified as differentially methylated across studies. [21][22][23][24][25][26] However, significant DNA methylation disruption of unique loci along with enrichment of key regulatory CpG regions has been documented across different study populations.…”
Section: Introductionmentioning
confidence: 99%
“…In support of this, exposure to arsenic induces alterations to the epigenome, including changes in CpG methylation and miRNA expression [18,[66][67]. The epigenome constitutes potentially heritable changes that influence gene expression but are not contained within the DNA sequence [18].…”
Section: Genetic and Epigenetic Underpinnings For Arsenic-associated Dmmentioning
confidence: 99%